2020
DOI: 10.3390/ijerph17051648
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Road Geometry on Vehicle Rollover and Skidding

Abstract: This paper analyzes the influence of single and combined unfavorable road geometry on rollover and skidding risks of D-class mid-sized sport utility vehicles (SUVs) with front-wheel drive for roads with design speeds at 80 km/h. A closed-loop simulation model of human-vehicle-road interactions is established to examine the systematic influence of road geometry on vehicle rollover and skidding. The effects of different road geometry on rollover and skidding on SUVs are studied for pavement surface with good and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
(38 reference statements)
2
23
0
Order By: Relevance
“…ADAMS is a simulation software for predicting the mechanical system performance, collision detection, motion range, and peak load. The quality of the simulation in ADAMS is high, and the modeling is complex [ 6 ]. The road was modeled by classical equations for circle and clothoid (also known as spiral) curves.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ADAMS is a simulation software for predicting the mechanical system performance, collision detection, motion range, and peak load. The quality of the simulation in ADAMS is high, and the modeling is complex [ 6 ]. The road was modeled by classical equations for circle and clothoid (also known as spiral) curves.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies indicate that most road accidents occur at horizontal curves [ 1 , 2 , 3 , 4 , 5 , 6 ]. At horizontal curves, the risk of accidents is significantly higher than that in other sections of the road [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stages of I and II can be connected by two opposite curves of equal length. Based on the characteristics of the vehicle's driving track, the transition curve coincides with the track of the vehicle's centroid, and the minimum radius of the curve at the connection is the minimum turning radius of the vehicle at the given speed [33].…”
Section: Figure3 Schematic Of the Vehicle Lane Changing Trackmentioning
confidence: 99%
“…The countries in these group have small number of vehicles used (less than 1% of worldwide). However, the number of deaths from road accidents is as high as 15% in these countries, unlike in high-income countries which possess as high as 40% of the world's vehicles but find less than 10% result in deaths [10], [11], [12], [13]. Therefore, it can be concluded that the income of the population affects the death rate from the road accident [14], [15].…”
Section: Introductionmentioning
confidence: 99%